Hydrodynamics and dissolved organic matter regulate partitioning behaviour of heavy metals in seawater in a human-impacted subtropical estuary - Zhang, Ling; Wu, Yunchao; Yang, Jia; Li, Pengju; Ni, Zhixin; Huang, Xiaoping (Environmental pollution (1987), 2025)
The partitioning behaviour of heavy metals (HMs) plays a crucial role in influencing their mobility and pollution risks in estuaries. However, this process remains poorly understood in dynamic estuaries subject to intense anthropogenic and terrestrial inputs, which substantially alter the hydrodynamics and organic matter characteristics. Here, we performed our study in the Pearl River Estuary, which records serious anthropogenic activities and contains vibrant hydrodynamic processes, via runoff alteration and organic matter component shift, with the aim of probing the partitioning mechanisms of HMs between the particulate and dissolved phases in the water column. Results indicated that the terrestrial and anthropogenic inputs via runoff primarily controlled the levels and distributions of HMs. Partition coefficients (Kd) of HMs were higher along the estuarine west coast and near river outlets, where stronger turbulence from currents and runoff prevailed. Offshore, Kd values decreased due to mixing of freshwater and seawater. Salt wedge-induced water stratification facilitated the retention of most HMs in the particulate phase, and had a moderate impact on metal partitioning during summer. Terrestrially derived humic-like organic components further induced the partitioning of most HMs towards the particulate phase during this season. Intense hydrodynamic mixing during winter favoured metal partitioning into the dissolved phase, increasing metal mobility and associated risks, particularly for As, Pb and Cr. Moreover, anthropogenically derived protein-like components promoted the presence of particulate phase HMs under reduced runoff conditions. This study advances the understanding of metal transfer, transformation and pollution risks in dynamic, human-impacted estuarine environments. [Display omitted] •Metal partitioning was investigated across contrasting hydrodynamic and DOM regimes.•Stratification moderately facilitated HMs combining with particulates in summer.•Mixing condition significantly promoted partitioning of HMs to dissolved phase.•Humic-like DOM in summer and protein-like DOM in winter drove HMs to particle phase.